2018
DOI: 10.4014/jmb.1707.07042
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Panduratin A on Periodontitis-Induced Inflammation and Osteoclastogenesis through Inhibition of MAPK Pathways In Vitro

Abstract: Periodontitis is an inflammatory disease caused by microbial lipopolysaccharide (LPS), destroying gingival tissues and alveolar bone in the periodontium. In the present study, we evaluated the anti-inflammatory and anti-osteoclastic effects of panduratin A, a chalcone compound isolated from , in human gingival fibroblast-1 (HGF-1) and RAW 264.7 cells. Treatment of panduratin A to LPS-stimulated HGF-1 significantly reduced the expression of interleukin-1β and nuclear factor-kappa B (NF-κB), subsequently leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Panduratin A and its derivatives have been shown to exhibit anti-tumor activity toward a number of cancer cell lines. 10,11,13,14,28,29) In contrast, panduratin A, 4-hydroxypanduratin A, and isopanduratin A inhibited TNF-α plus actinomycin D-induced cell death in L929 cells. 30) Panduratin A and 4-hydroxypanduratin A have also been shown to reduce L-glutamate toxicity in N18-RE-105 cells.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Panduratin A and its derivatives have been shown to exhibit anti-tumor activity toward a number of cancer cell lines. 10,11,13,14,28,29) In contrast, panduratin A, 4-hydroxypanduratin A, and isopanduratin A inhibited TNF-α plus actinomycin D-induced cell death in L929 cells. 30) Panduratin A and 4-hydroxypanduratin A have also been shown to reduce L-glutamate toxicity in N18-RE-105 cells.…”
Section: Resultsmentioning
confidence: 92%
“…Panduratin A has been shown to inhibit LPS-induced IκBα phosphorylation and its degradation in RAW264.7 cells, 12) as well as the TNF-α-stimulated translocation of p65 and p50 to the nucleus in A549 cells. 13,14) A previous study reported that panduratin A reduced the expression of NF-κB in LPS-stimulated gingival fibroblast-1 cells. 15) Collectively, these findings indicated that panduratin A inhibited the NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the anti-osteoclastic activities of CXS and XAN, we used RAW264.7 cells with RANKL as an osteoclastogenesis inducer [5]. RANKL treatment elevated both the protein and mRNA levels of the osteoclastic transcription factors and bone degradation enzymes, NFATc1, c-Fos, cathepsin K, and TRAP, whereas CXS and XAN treatments decreased the expression levels (Figs.…”
Section: Cxs and Xan Inhibit Osteoclastogenesis In Rankl-treated Raw2mentioning
confidence: 99%
“…The interaction between LPS and TLR activates the nuclear factor kappa B (NF-κB) or mitogen-activated protein kinase (MAPK)/activator protein-1 (AP-1) signaling pathway [4]. The NF-κB and MAPK/AP-1 pathways subsequently upregulate interleukin (IL)-1β, a major cytokine, and matrix metalloproteinases (MMPs), which are protein degradation enzymes, consequently destroying the periodontal ligament [4,5].…”
Section: Introductionmentioning
confidence: 99%